Satisfaction of high school students with a mobile game-based English learning system. (2017) - Tsai, Chia Hui; Cheng, Ching-Hsue; Yeh, Duen-Yian; Lin, Shih-Yun
This study investigated the satisfaction of high school students with a mobile game-based English learning system. The system, called the Happy English Learning System (HELS), integrates learning material into a game-based context and was constructed and installed on mobile devices to conduct an experiment over a period of eight weeks. The experimental sample comprised 38 students. Through statistical analysis, the results confirmed the merits of a mobile game-based approach for high school students learning English. The findings included the following: (1) the adoption of a familiar, but challenging game design is a critical technical factor; (2) the students that were more interested in learning English were more satisfied with this approach; (3) regardless to what extent the students were interested in playing games or enjoyed playing the HELS, they acknowledged satisfaction with the system and the learning process; and (4) the more time the students spent playing the HELS per week, the more satisfied they were with the system and the learning process. Finally, several suggestions are proposed for future applications.